2011
DOI: 10.3171/2011.2.peds10505
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for children with treatment-resistant epilepsy: a consecutive series of 141 cases

Abstract: Object The authors undertook this study to analyze the efficacy of vagus nerve stimulation (VNS) in a large consecutive series of children 18 years of age and younger with treatment-resistant epilepsy and compare the safety and efficacy in children under 12 years of age with the outcomes in older children. Methods The authors retrospectively reviewed 141 consecutive cases involving children (75 girls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
1
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 55 publications
8
109
1
13
Order By: Relevance
“…This volume of information has been used to establish trends in outcome not otherwise evident in investigations with smaller sample sizes. Focal epileptogenic foci and the presence of cortical malformations have been shown to be positive predictors of success with VNS treatment by multiple investigators, including Elliott et al, 10,11 Janszky et al, 19 and Ghaemi et al, 15 but the issue of most appropriate age of implantation appears to remain subject to argument. Ghaemi et al found younger age at initiation of treatment to be a positive predictor, whereas both Elliott et al and Murphy et al found no statistical correlation between younger age and positive outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This volume of information has been used to establish trends in outcome not otherwise evident in investigations with smaller sample sizes. Focal epileptogenic foci and the presence of cortical malformations have been shown to be positive predictors of success with VNS treatment by multiple investigators, including Elliott et al, 10,11 Janszky et al, 19 and Ghaemi et al, 15 but the issue of most appropriate age of implantation appears to remain subject to argument. Ghaemi et al found younger age at initiation of treatment to be a positive predictor, whereas both Elliott et al and Murphy et al found no statistical correlation between younger age and positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…There were 14 publications that used this standard, and of the 1378 patients studied, a mean of 50.9% (range 18.4%-67%) showed a 50% or greater decrease in seizure frequency. 1,2,4,5,[8][9][10][11]15,[24][25][26][27][28] Five of the remaining studies used the mean or median frequency reduction from baseline. 3,14,17,22,23 The mean seizure reduction in these investigations was 42.8% (range 28%-66%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rezektif cerrahiye aday olmayan ve ilaca dirençli fokal (sekonder jeneralizasyon olsun ya da olmasın) veya jeneralize nöbetleri devam eden çocuklarda nöbet sıklığını azaltmaya yönelik ek tedavi olarak endikedir. [1,2,[4][5][6] Amerikan gıda ve ilaç kurumu (FDA) 1997 yılında 12 yaş üzeri çocuklar için ek tedavi olarak VSS'yi uygun görmüştür. O zamandan günümüze yapılan çalışma-ların çoğu, VSS'nin klinik etkinliğini erişkin hastalarda değerlendirmiştir.…”
Section: Vagal Sinir Stimülasyonuunclassified
“…When comparing patients younger and older than 12 years, no significant difference in efficacy or complication rate was demonstrated after five years of follow-up in 141 patients 39 , although some reported increased infection rates in children 40 . Predictors of response have not been completely clarified, although some elements may have a prognostic value.…”
mentioning
confidence: 99%